THE UNDERSTANDING OF DIARRHOEAL DISEASES BY THE POPULATION: EVOLUTIONARY TRENDS OF EPIDEMIOLOGICAL INDICATORS OF DIARRHOEAL DISEASES IN THE HEALTH ZONE OF KINDU - Bonny , ASSANI WAKENGE; ONYANGO , ROSEBELLA; OTIENO , CAREENA; Grace, KAMANA LELA; Thomas, MIANI BIKENGE; Hattie, NKAMBA NKANKOLONGO; Isaac , NKAMBA WA NKAMBA; Charles, WASONGA MUPENDA; Alphonse, MASANDI MILONDO (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
Diarrheal diseases are a major public health problem for the Democratic Republic of Congo in general. Despite consistently high morbidity and mortality, endemic diarrheal disease remains under-documented. WHO estimates that there are 1.4 to 4.3 million cases of diarrhoeal diseases each year, with 28,000 to 142,000 deaths worldwide. The Kindu health zone is experiencing the repetitive appearance of cases of diarrheal diseases in epidemic mode, which motivated this research to determine the population's perception of diarrheal diseases in the Kindu health zone: path health problems.A case-control study with 134 cases and 134 age- and sex-matched controls was conducted after the outbreak of recurrent diarrheal diseases from 2020 to 2021 experienced in this health zone. Cases were selected by systematic sampling from linear lists in the Kindu health zone, and controls were selected in the community in a simple random manner from plots adjacent to the cases.  Odds ratio (OR) calculation with its confidence interval and logistic regression were used to identify risk factors for Diarrhoeal Disease.A focus on providing clean water, toilet sanitation and behavior change communication in a comprehensive program would help prevent diarrheal diseases in the Kindu health zone.